1979
DOI: 10.1080/02541858.1979.11447656
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Maternal and Neonatal Behaviour in the Captive Reticulated Giraffe

Abstract: A captive reticulated giraffe was observed constantly for three weeks prior to, and periodically for 90 days subsequent to, the birth of her calf. Extensive observations were made of the birth sequence, feeding, drinking, sleeping and one instance of an infant distress call, as well as observations of the initiation of maternal behaviour (including licking, nursing, placentophagia, and what appeared to be helping the calf to stand, guiding the calf's movements, and attempts to respond to the calf's distress ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In addition, Langman [1977, 19821 has indicated that giraffes have a very specific and unique mother-infant relationship based on the giraffe's unusual physiology. Of the two main early ungulate mother-infant contact systems, some calves are "followers" of their mothers immediately after birth while others are "hiders," ie, the newborn calves remain hidden most of the time during the first weeks while the mothers feed and return at intervals to nurse them [Lent, 1974;Langman, 1977;see Walther in Langman, 19771. Both the giraffe and okapi are of the hider type.…”
Section: Giraffe Mother-infant Stategy: Supportive Field Datamentioning
confidence: 99%
“…In addition, Langman [1977, 19821 has indicated that giraffes have a very specific and unique mother-infant relationship based on the giraffe's unusual physiology. Of the two main early ungulate mother-infant contact systems, some calves are "followers" of their mothers immediately after birth while others are "hiders," ie, the newborn calves remain hidden most of the time during the first weeks while the mothers feed and return at intervals to nurse them [Lent, 1974;Langman, 1977;see Walther in Langman, 19771. Both the giraffe and okapi are of the hider type.…”
Section: Giraffe Mother-infant Stategy: Supportive Field Datamentioning
confidence: 99%
“…(1984) recommended that obstetrical examination be carried out after 2 h of active parturition without noticeable signs of progress. This is supported by Dagg and Foster (1982) who stated that a giraffe calving should last between 1 and 2 h. However,Kristal and Noonan (1979) observed a parturition lasting approximately 15 h, with no fetal protrusion shown during the first 14 h, but a healthy calf being born uneventfully. The practicality of intervention is dependent on the facilities available and other factors also need to be considered.…”
Section: Discussionmentioning
confidence: 69%
“…Duration of parturition can be an indicator of dystocia (Treacy et al , 2006). However, Giraffe parturition lasting over 15 hours has been reported without any apparent distress (Kristal & Noonan, 1979), potentially indicating that duration of labour is not a factor in Giraffe dystocia. Most parturition events leading to calf rejection in this survey were within the standard labour duration for the species (2–4 hours) (Bercovitch & Berry, 2015), with the exception of one 7 hour labour.…”
Section: Discussionmentioning
confidence: 99%